Utility of brain natriuretic peptide in the neonatal pathologies - Deshpande, Shriprasad R. (International Journal of Contemporary Pediatrics, 2020)
This is with reference to the recently published article titled ‘N-terminal pro brain natriuretic peptide as a marker of myocardial dysfunction in newborns with perinatal asphyxia’ by Drs. Kariyappa et al.